RELIGIOUS COGNITIVE BEHAVIOR COUNSELING TO INCREASE SUBJECTIVE WELLBEING IN ADOLESCENTS SURVIVOR OF FAMILY VIOLENCE - Mutingatu Sholichah; Sri Kushartati; Erny Hidayati (UIN Sunan Kalijaga, 2020)
Abstract. Family plays an important role in nurturing and guiding adolescents to develop their identity and character. However, for adolescents who have grown up in families that experienced conflict or even violence, they have an increased risk to develop both internalizing and externalizing problems which lead to their lower Subjective Wellbeing (SWB). Group counseling with a cognitive behavioral approach known as religious cognitive behavior counseling (RCBC) using Islamic prayer implementation, was applied to change negative cognitive distortion or self-talk, in adolescents who experienced family violence. Using experimental study, the RCBC was expected to help participants improving their well-being. Pretest and posttest were executed to measure their subjective well-being before and after the counseling for 40 participants. The results showed that RCBC significantly increased positive affect with the value of t = -2.658; p-0.005. The RCBC can be developed as an alternative intervention to increase SWB in adolescents particularly in Moslem community.Keywords: Adolescents, group counseling, religious cognitive behavior, subjective wellbeingAbstrak. Keluarga memiliki peran penting dalam proses pendewasaan dan pembimbingan remaja untuk mengembangkan identitas dan karakter mereka. Akan tetapi, remaja yang tumbuh dalam keluarga yang mengalami konflik atau bahkan kekerasan. Mereka memiliki peningkatan resiko dalam mengembangkan masalah internal dan eksternal yang menuntun mereka pada Kesejahteraan Subjektif (SWB). Konseling kelompok menggunakan sebuah pendekatan perilaku kognitif yang dikenal dengan Religious Cognitive Behavior Counseling (RCBC) menggunakan implementasi berdoa secara Islam, yang digunakan untuk mengubah distorsi kognitif atau self-talk pada remaja yang mengalami kekerasan di rumah. Penelitian kali ini menggunakan studi eksperimen dengan RCBC yang diharapkan membantu subjek meningkatan kesejahteraan subjektifnya. Pre-tes dan pos-tes dilakukan untuk mengukur keadaan kesejahteraan subjektif sebelum dan sesudah pada 40 subjek. Hasil menunjukkan bahwa RCBC secara signifikan berpengaruh positif dengan nilai t = -2.658; p-0.005. Kesimpulannya, RCBC dapat dikembangkan sebagai sebuah intervensi alternatif untuk meningkatkan kesejahteraan subjektif pada remaja khususnya pada komunitas Muslim.Kata Kunci: Remaja, konseling kelompok, perilaku kognitif beragama, kesejahteraan subjektif